Cyprus and Cyrene, two sides of the same coin: an examination of the role of the gymnasion in two Ptolemaic possessions - Stavrou, Dorothea (Journal of Greek Archaeology, 2025)
During the Hellenistic period, the gymnasion became a principal civic institution of the polis, integral to the Greek way of life. In the gymnasia citizens and free young men received athletic, intellectual and military training.1 They participated in athletic and religious activities and festivals, thereby reinforcing their civic identity and social unity. During the period of the Successors, the gymnasion spread through the newly-conquered territories of the East, mainly as an answer to the particular needs of Greco-Macedonian settlers and soldiers of royal armies. Thus the institution lost its original narrow civic character and now appeared outside the confines of the polis in urban and rural territories, in cities, villages and military settlements. The diffusion of the gymnasion in the East, where the Greek element was in the minority, changed its role, function and impact.